Measurement of Information System Quality Management using ISO 9001:2015 Standards at PT Bersama Kita Besar - Adrianus Kelvin; Wella Wella (G-Tech: Jurnal Teknologi Terapan, 2024)
Operational problems related to performance evaluation within the company are the background for this research. Data was collected through interviews with the chief auditor, a 4-item questionnaire for the head of IT and 3 IT staff, and observations of company documents and staff performance. The questionnaire used a Likert scale, and the overall assessment applied the Maturity Model. Results indicated that PT. Bersama Kita Besar achieved a level 3 (Defined Process) in maturity. Small improvements are needed to reach levels 4 and 5, such as enhancing staff performance through training and adding competent human resources. The study focused on the IT division of PT Bersama Kita Besar, using clauses 4 to 10 of ISO 9001:2015 for measurement. These results can support the company's ISO 9001:2015 certification efforts and ongoing improvements.